Maternal immunization impairs lymphoma growth and CNS/ocular metastasis in the offspring - Ori Braitbard; Ori Braitbard; Allan Bar-Sinai; Jacob Hochman (Frontiers in Immunology)
Maternal immunization is an important tool directed against a variety of infectious maladies in the offspring. A complementary, but less explored area is the use of maternal immunization in the prevention and treatment of childhood cancers. This in part stems from the lack of adequate experimental model systems. Lymphomas of the Central Nervous System (CNS) and ocular involvement pose a therapeutic challenge. Ocular lymphoma is a lethal disease caused mainly by two clinically distinct forms of non-Hodgkin’s lymphoma: non-Hodgkin’s lymphoma of the central nervous system, or Primary CNS lymphoma (PCNSL), and systemic lymphoma metastatic to the eye. Previously, we developed an experimental model whereby mouse lymphoma cell variants, derived from the S49 T-cell lymphoma, metastasized to the CNS and eyes following Intraperitoneal inoculation at days 7-10 postnatal. Here, we extended the model to study whether maternal immunization can impede CNS/Ocular metastasis in the offspring exposed to the metastatic lymphoma cells. To that effect, female Balb/C mice were vaccinated with either immunogenic, live, S49 lymphoma cell variants, or with a purified protein antigen: the 98 amino acid signal peptide of the envelop precursor protein of Mouse Mammary Tumor Virus (MMTV) endogenously harbored by the S49 lymphoma. The offspring from both vaccination protocols were immunized against a challenge with the CNS/Ocular metastatic lymphoma cells. Immunity was conferred via milk suckling and was prolonged without further challenge for an extended period of at least 3 months. The abovementioned findings constitute a novel experimental model system whereby CNS/Ocular metastasis of malignant lymphoma in the offspring is impeded through maternal vaccination/immunization and thus, can be followed mechanistically as well as for novel therapeutic modalities.